Pattern of Metastasis in Cervical Lymph Nodes and Topographic Distribution of Primary Site: Study of 375 Case - Dr. Dhaval Jetly; Dr. Siddharth Thummar (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Lymph nodes are the most common site of metastatic malignancy and presence of metastatic tumor in lymph nodes is essential for the management and prognosis of cancer. Cervical lymph node metastasis most commonly develop from oral cavity malignancies. Tumors of Upper Aerodigestive tract, Salivary and Thyroid glands and any other sites of the body can present as cervical nodal metastasis. The topographic correlations are helpful clues to the most common sites of origin of metastases in cervical lymph nodes.Objectives: (1) Typing of Metastatic Tumor, its Prevalence and Demographic Incidence in cervical lymph nodes. (2) Distribution of Cervical lymph node metastasis & Relevance to probable Primary Site.Methodology: In the study, FNAC and/or Biopsy were taken from enlarged cervical lymph nodes to confirm the metastatic tumor and to type the tumor. IHC was done whenever necessary for diagnosis and to confirm the primary site. Relevant clinical details and patient history were collected from patients’ case file and electronic patients’ records. Total 375 malignant metastatic cases were included in the study for analysis.Conclusion: SCC from head and neck region is the most common metastatic malignancy present in the cervical lymph nodes. SCC from Lung, Esophagus or Cervix can also present as metastatic lymph node. Adenocarcinoma and Neuroendocrine carcinoma from Lung or GI Tract in Males & Ductal Carcinoma of Breast and Papillary Thyroid Carcinoma in Females can also involve Neck Lymph nodes.